Implementasi Program Pengembangan Perikanan Tangkap Pada Dinas Pertanian Dan Perikanan Kota Pekanbaru - Eko Handrian; Siti Hawa (Universitas Muhammadiyah Mataram, 2022)
This study aims to determine and implement the Capture Fisheries Development Program at the Pekanbaru City Agriculture and Fisheries Service, the assessment indicators used include Policy Standards and Targets, Resources, Inter-Organizational Relations, Characteristics of Implementing Agencies, Social, Political and Economic Conditions. This type of research uses descriptive quantitative research methods with data collection techniques used consisting of primary data collected by questionnaires and interviews, and secondary data collected using observation and documentation. Based on the results of the research, it is known that in this study from the side of the official apparatus that the implementation of the Capture Fisheries Development program at the Pekanbaru City Agriculture and Fisheries Service is